A strategic approach using representative lv networks in the assessment of technical losses on LV network with solar photovoltaic - Tang J.H.; Au M.T.; Shareef H.; Busrah A.M. (Insight Society, 2023)
Low voltage network (LVN) forms an extensive part of the distribution network as it is used to connect electricity supply from utility substations to diverse segments of loads in different geographic locations. With the increasingly high penetration of solar PV in LVN, utility companies are finding it necessary to establish the contribution of this solar PV to the overall technical losses in the distribution network. This paper presents a strategic approach using representative LVN to determine the impact of solar PV on technical losses on the LVN. Five types of representative LVN characterized by different customer load segments (domestic, commercial and industrial) and peak load demand were developed. The impact on technical losses of solar PV connected to these representatives LVN was assessed on a statistical basis for a supply zone. The results obtained are consistent and could be applied to establish investment strategies on the distribution network, tariff revision exercise and optimization of distribution network planning/design.